2018
DOI: 10.1590/1984-6487.sess.2018.28.06.a
|View full text |Cite
|
Sign up to set email alerts
|

“Lo quería hacer rápido, lo quería hacer ya”: tiempos e intervalos durante el proceso de aborto

Abstract: Resumen Este artículo se propone, desde una perspectiva cualitativa, describir y analizar los tiempos durante el proceso de aborto en mujeres residentes en el Área Metropolitana de Buenos Aires, en base a cinco entrevistas en profundidad. Encontramos, en primer lugar, que el tiempo de gestación funciona como un cronómetro, que avanza de modo tan apremiante como la voluntad de interrumpirlo. En segundo lugar, identificamos el aborto como un proceso atravesado por los siguientes intervalos: 1) noticia del embara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 18 publications
1
23
0
4
Order By: Relevance
“…Most of these studies described people obtaining the pills through online telemedicine services and other online vendors (10,37,40,67,(70)(71)(72)(74)(75)(76)(77)(78)(79)(80), while others obtained them through their social networks or over the counter at pharmacies (43,68,(81)(82)(83)(84) One study mentions informal doctors ("non-allopath doctors") as sources of procurement (82). Studies reported fear of online procurement among some participants, including fear of being scammed and receiving fake pills (37), and worries that the pills might be confiscated at customs (10,76).…”
Section: Mifepristone + Misoprostolmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of these studies described people obtaining the pills through online telemedicine services and other online vendors (10,37,40,67,(70)(71)(72)(74)(75)(76)(77)(78)(79)(80), while others obtained them through their social networks or over the counter at pharmacies (43,68,(81)(82)(83)(84) One study mentions informal doctors ("non-allopath doctors") as sources of procurement (82). Studies reported fear of online procurement among some participants, including fear of being scammed and receiving fake pills (37), and worries that the pills might be confiscated at customs (10,76).…”
Section: Mifepristone + Misoprostolmentioning
confidence: 99%
“…Sources of procurement and/or information included online vendors (13,39,47,50,77,78,89), telephone vendors (47,88), friends and relatives (13,36,47,51,61,66,78,(88)(89)(90), accompaniment groups(89), pharmacists (over the counter purchase with or without prescription) (13,28,36,41,43,47,51,53,66,68,78,79,(90)(91)(92)(93)(94)(95)(96)(97), doctors or nurses (13,28,39,43,47,51,53,61,66,78,88,…”
Section: Misoprostol Onlymentioning
confidence: 99%
See 3 more Smart Citations